2022
DOI: 10.1088/1748-0221/17/03/p03010
|View full text |Cite
|
Sign up to set email alerts
|

Setup of Compton polarimeters for measuring entangled annihilation photons

Abstract: An experimental setup for studying the Compton scattering of annihilation photons in various (entangled and decoherent) quantum states is presented. Two entangled γ-quanta with an energy of 511 keV and mutually orthogonal polarizations are produced by positron-electron annihilation in a thin aluminum plate and are emitted in opposite directions. To measure both photons, the setup provides two equivalent arms of Compton polarimeters. A Compton polarimeter consists of a plastic scintillation scatt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…It is worth mentioning that the obtained results [16] do not agree with the theoretical predictions [19]. Recently, Abdurashitove et al [17], reported experimental results that contradicted those of obtained by Watts et al [16]. The experiments were performed using the same methodology: (a) when their relative linear polarization was considered to be entangled (direct Compton kinematics applied to backto-back photons to measure the correlation), (b) inducing decoherence in the polarization entanglement, using the scatterer along the path of one of the photons, and calculating the effect on the measured correlation.…”
Section: Recent Results Of Experimental Measurements Leading Towards ...mentioning
confidence: 71%
See 4 more Smart Citations
“…It is worth mentioning that the obtained results [16] do not agree with the theoretical predictions [19]. Recently, Abdurashitove et al [17], reported experimental results that contradicted those of obtained by Watts et al [16]. The experiments were performed using the same methodology: (a) when their relative linear polarization was considered to be entangled (direct Compton kinematics applied to backto-back photons to measure the correlation), (b) inducing decoherence in the polarization entanglement, using the scatterer along the path of one of the photons, and calculating the effect on the measured correlation.…”
Section: Recent Results Of Experimental Measurements Leading Towards ...mentioning
confidence: 71%
“…In this study, the scattering angle range was 80 0 < θ 1 = θ 2 < 100 0 for both cases. Details of the experiments can be found in the respective publications [16,17] It should be emphasised that in the work of Abdurashitov et al [17], no difference in the µ distribution was observed for the entangled and separable quantum states, indicating that the Compton kinematics remained identical for both cases as predicted in [19]. Fig.…”
Section: Recent Results Of Experimental Measurements Leading Towards ...mentioning
confidence: 77%
See 3 more Smart Citations